Association between the type of physical activity and metabolic syndrome in middle-aged and older adult residents of a semi-mountainous area in Japan - Noriko Kudo; Ritsuko Nishide; Mayumi Mizutani; Shota Ogawa; Susumu Tanimura (Komiyama Printing Co. Ltd, 2021)
Abstract Background Physical activity is reported to prevent metabolic syndrome. However, it is unclear whether exercise or daily physical activity is more beneficial for residents of semi-mountainous areas. This study aimed to identify whether daily physical activity is more beneficial than exercise for the prevention of metabolic syndrome among middle-aged and older residents in semi-mountainous areas. Methods We analyzed secondary data of 636 people who underwent a specific health checkup in a semi-mountainous area of Japan. Physical activity was classified into four types: inactivity (I-type; without exercise and without daily physical activity), only exercise (E-type; with exercise and without daily physical activity), only daily physical activity (D-type; without exercise and with daily physical activity), and full physical activity type (F-type; with exercise and with daily physical activity). We compared the means of risk factors for metabolic syndrome by these four types, followed by logistic regression analysis, to identify whether and to what extent the D-type was less likely to have metabolic syndrome than the E-type. Results The prevalence of metabolic syndrome was 28.5% (men 45.7%, women 15.8%). The proportions of men with exercise and daily physical activity were 38.7% and 52.8%, respectively. For women, the proportions were 33.0% and 47.1%, respectively. In women, the D-type had the significantly lowest BMI, smallest waist circumference, highest HDL-C, and lowest prevalence of metabolic syndrome of the four types; the same was not observed in men. Additionally, D-type activity was more strongly associated with a reduced risk of metabolic syndrome than E-type activity in women (adjusted odds ratio 0.24; 95% confidence interval 0.06-0.85, P = 0.028). Conclusions Compared to middle-aged and older women residents with exercise in a semi-mountainous area of Japan, those with daily physical activity may effectively prevent metabolic syndrome.